Photographic Record of a Melanistic Spotted Deer Axis axis (Erxleben) in Parambikulam Tiger Reserve, Kerala, India - Kumar, Sanjayan (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.